2022
DOI: 10.3389/fmed.2022.832713
|View full text |Cite
|
Sign up to set email alerts
|

PEP-sNASP Peptide Alleviates LPS-Induced Acute Lung Injury Through the TLR4/TRAF6 Axis

Abstract: Acute lung injury (ALI) is a severe inflammatory lung disease associated with macrophages. Somatic nuclear autoantigenic sperm protein (sNASP) is a negative regulator of Toll-like receptor (TLR) signaling that targets tumor necrosis factor (TNF) receptor-associated factor 6 (TRAF6) in macrophages, which is required to maintain homeostasis of the innate immune response. In the present study, we generated a cell permeable PEP-sNASP peptide using the sNASP protein N-terminal domain, and examined its potential the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Silencing NASP also enhanced NF-κB activity in response to HDM ( Figure 3 B). Since PEP-NASP, as a cell-permeable peptide, can selectively inhibit TLR4-mediated TRAF6/NF-κB signaling pathways [ 27 ], we decided to evaluate whether the transduced PEP-NASP peptide would affect TRAF6 downstream signaling following an HDM stimulation. The results indicated that the treatment of the PEP-NASP peptide, but not the control NASP peptide, diminished the HDM-induced phosphorylation of p38 MAPK and p65 ( Figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Silencing NASP also enhanced NF-κB activity in response to HDM ( Figure 3 B). Since PEP-NASP, as a cell-permeable peptide, can selectively inhibit TLR4-mediated TRAF6/NF-κB signaling pathways [ 27 ], we decided to evaluate whether the transduced PEP-NASP peptide would affect TRAF6 downstream signaling following an HDM stimulation. The results indicated that the treatment of the PEP-NASP peptide, but not the control NASP peptide, diminished the HDM-induced phosphorylation of p38 MAPK and p65 ( Figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
“…The HDM extract ( D. pteronyssinus/ D. farinae extract mix) was purchased from Citeq (#20.50.85, Groningen, The Netherlands). Preparation of the PEP-NASP and NASP peptides was previously described in [ 27 ]. PEP-NASP or NASP peptides (0.4 μM) were added to the culture medium for 1 h before HDM treatment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations